Industry-level heterogeneity analysis. - Yuanbo Hu (10142927) (2025)
As the Fourth Industrial Revolution advances, technological innovation has emerged as a key driver for firms to shape core competitiveness. The corporate governance literature recognizes CEO personality traits as key determinants of a firm’s technological innovation. Drawing on Upper Echelons Theory and Behavioral Agency Theory, this study investigates the effect of CEO greed on corporate technological innovation using a sample of China’s A-share companies listed on the Shanghai and Shenzhen stock exchanges from 2011 to 2023. We find that: (1) CEO greed significantly fosters corporate technological innovation. (2) Analyst coverage strengthens the positive relationship between CEO greed and corporate technological innovation. (3) This effect varies significantly across different firms and industries. (4) CEO greed significantly promotes exploitative (shorter-cycle) innovation, but has no significant effect on exploratory (longer-cycle) innovation.